2016
DOI: 10.1200/jco.2015.61.0733
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Trial of Low-Dose Morphine Versus Weak Opioids in Moderate Cancer Pain

Abstract: Purpose The WHO guidelines on cancer pain management recommend a sequential three-step analgesic ladder. However, conclusive data are lacking as to whether moderate pain should be treated with either step II weak opioids or low-dose step III strong opioids. Patients and Methods In a multicenter, 28-day, open-label randomized controlled study, adults with moderate cancer pain were assigned to receive either a weak opioid or low-dose morphine. The primary outcome was the number of responder patients, defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(92 citation statements)
references
References 28 publications
4
79
0
9
Order By: Relevance
“…Of the 41 patients who underwent radical cystectomy in the study by Balar et al . 86 , 26 (63.4%) had <pT2N0 disease and, importantly, the vascular toxicity was similar to that observed in neoadjuvant trials of standard-dose GC chemotherapy. In an intention-to-treat analysis (with patients who refused radical cystectomy counted as nonresponders), the <pT2N0 rate was 56.5% 86 .…”
Section: Improving On Standard Nact With Mvacsupporting
confidence: 71%
See 2 more Smart Citations
“…Of the 41 patients who underwent radical cystectomy in the study by Balar et al . 86 , 26 (63.4%) had <pT2N0 disease and, importantly, the vascular toxicity was similar to that observed in neoadjuvant trials of standard-dose GC chemotherapy. In an intention-to-treat analysis (with patients who refused radical cystectomy counted as nonresponders), the <pT2N0 rate was 56.5% 86 .…”
Section: Improving On Standard Nact With Mvacsupporting
confidence: 71%
“…On the basis of the promising activity and toxicity profiles of dose-dense GC (ddGC) compared with that of ddMVAC reported in the metastatic setting 84 (TABLE 3), two prospective, multicentre phase II studies of neoadjuvant ddGC (2-week cycle) chemotherapy in patients with MIBC have been initiated and reported in abstract form 85,86 . Plimack et al 85 reported that, among the first 13 patients treated in one of these trials, two patients had a myocardial infarction resulting in congestive heart failure, one had a deep venous thrombosis (DVT), one had a pulmonary embolus, and one required coronary artery bypass grafting before surgical resection of the tumour 85 .…”
Section: Improving On Standard Nact With Mvacmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1986, the WHO three-step ‘ladder’ has recommended weak opioids for patients with moderate pain 26. Recent researches have revealed that passing directly from step I to step III of the WHO analgesic ladder is more efficient than the traditional three-step strategy for mild–moderate chronic cancer pain 25 26.…”
Section: Discussionmentioning
confidence: 99%
“…If the pain improves, the dose should be calculated for 24 h and divided into 4-6 h intervals [40]. In a recent randomized trial, Bandieri et al [42] concluded that in patients with cancer and moderate pain, low-dose morphine significantly reduced the intensity of pain compared with weak opioids, with similarly good tolerability and an earlier effect.…”
Section: • Morphinementioning
confidence: 99%